The Infleunce of the Subtituent on the Kinetic of Amino Acids Oxidaition by permanganate Ion - Ibrahim Y.M.Al-Tayy; Rana A.A.A.Quba; Mahmoud S.Sajeed (College of Education for Pure Sciences, 2005)
The kinetics of the oxidation of nine amino acids (glycine, alanine, valine. leucine, norleucine, serine, threonine, spartic and lysine) by permanganate ion were studied in an aqueous medium. The results showed that the oxidation reaction proceeds through two different pathways, The first is noncatalyzed and the second is autocatalyzed by the colloidal inorganic product (MnO2). The rate of the noncatalyzed reaction is first-order in concentration of both amino acid and oxidizing agent, while the autocatalyzed reaction is first-order in concentration of amino acid, oxidizing and autocatalytic agent. Depending on the relation between the rate constant and temperature the thermodynamic parameters for the two pathways were calculated. A special care has been given to the effect of the structure of the group attached to chiral carbon atom of the amino acids on the rate and mechanism of oxidation reactions. Thekinetic results gave evidences supporting the proposed mechanism for the reaction, On the other hand, by measuring the rate of oxidation at different pH medium, the rate constant of oxidation of ananionic and zwitterionic form are calculated.